GAMBARAN PENGETAHUAN IBU HAMIL TENTANG ANEMIA DI PUSKESMAS RUMBIO JAYA 2024 - Naziroh, Maysah; Harahap, Dewi Anggriani; Yusnira, Yusnira (Evidence Midwifery Journal, 2025)
In Indonesia, the maternal mortality rate (MMR) is one of the indicators of the success and health status of mothers. According to the World Health Organization (WHO) in 2020, around 41.8% of pregnant women worldwide experience anemia, mainly due to iron deficiency. Data from the 2018 Riskesdas stated that 48.9% of pregnant women in Indonesia with anemia experienced anemia. This study aims to determine the Description of Pregnant Women's Knowledge About Anemia at the Rumbio Jaya Health Center in 2024. The design of this study used analytical observation with a Descriptive design. Respondents in this study were 74 pregnant women. The sampling technique used was Incidental Sampling. The results showed that the level of knowledge of pregnant women about anemia at the Rumbio Jaya Health Center was mostly in the category of not knowing, which was 25.7%, and knowing as much as 74,.3%. Pregnant women who do not know with the highest percentage (54.1%) are about the causes and dangers of anemia and good knowledge with the highest percentage (54.1%) is about the signs and symptoms of anemia. It is expected that health workers at the Rumbio Jaya Health Center, especially TPG, will further improve the knowledge of pregnant women about anemia, especially about preventing anemia in pregnant women and pregnant women at the Rumbio Jaya Health Center who will further improve their knowledge about anemia and apply it to their daily lives so that mothers can avoid anemia